2011
DOI: 10.2220/biomedres.32.135
|View full text |Cite
|
Sign up to set email alerts
|

Plasma miR-124 as a biomarker for cerebral infarction

Abstract: MicroRNAs (miRNAs) are endogenous small RNAs that play an important role in various physiological processes by downregulating target genes. Recently, plasma miRNAs have been investigated as biomarkers for various diseases. In this study, miRNA array analysis in various tissues showed that miR-124 is almost exclusively expressed in the central nervous system and neuronal cells, suggesting that it might be useful as a potential biomarker for neurological diseases. We examined whether plasma concentrations of bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 30 publications
1
86
1
4
Order By: Relevance
“…[19][20][21][22][23][24] Recently, plasma miR-124 was found to be elevated in rats after cerebral ischemia, suggesting its potential role as biomarker for cerebral infarction. 25,26 miR-124 can target a large number of mRNAs, [27][28][29] such as cyclin-dependent kinase 6, laminin γ1, Lhx2, and Sox9. 21,[30][31][32] Hence, miR-124 may have multiple and complex roles in cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23][24] Recently, plasma miR-124 was found to be elevated in rats after cerebral ischemia, suggesting its potential role as biomarker for cerebral infarction. 25,26 miR-124 can target a large number of mRNAs, [27][28][29] such as cyclin-dependent kinase 6, laminin γ1, Lhx2, and Sox9. 21,[30][31][32] Hence, miR-124 may have multiple and complex roles in cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…At 0 and 6 h following ligation and sham operation (n = 5; each operation), rats were anesthetized with pentobarbital, and blood was collected for further miRNAs and CPK analysis. cardium-specific miRNAs are excellent biomarkers for myocardial infarction (1,22), and plasma concentrations of brain-specific miRNA can serve as a biomarker for cerebral infarction (38). In the present study, we focused on the miRNA expression in muscular tissues and assessed whether expression profiling of miRNAs in various muscle cells may be useful for the diagnosis of diseases involving muscle cells.…”
Section: Assessment Of Plasma Mirnas As Biomarkers For Muscular Injurmentioning
confidence: 99%
“…Jeyaseelan et al [16] demonstrated a large elevation in circulating miR-290 at 24 hours after reperfusion in rats subjected to middle cerebral artery occlusion. In similar rat models of stroke, Liu et al [17] demonstrated increases in miR-10a, miR-182, miR-200b and miR-298 in both blood and brain 24 hours following ischemia/ reperfusion [17], while Weng et al [137] measured an increase in plasma levels of miR-124 as early as 6 hours following reperfusion. Unfortunately these studies did not demonstrate changes in the miRNA profile in the period immediately following ischemia, prior to reperfusion, which would be clinically relevant in determining a diagnosis and instituting treatment in people suffering acutely from stroke.…”
Section: G Mirnas As Biomarkersmentioning
confidence: 98%